Analysis of the Implementation of Tax Planning to Minimize Income Tax Burden at PT MAP Boga Adiperkasa Tbk in 2022 - Khalida Sofia Sofia; Memen Kustiawan; Ida Farida (Universitas Muhammadiyah Makassar, 2024)
The obligation to pay taxes applies not only to personal taxpayers, but also to business entities. Implementation Taxpayers must pay, deposit, and report tax calculations under the self-assessment system. However, business entities have different interests from the government in terms of taxes. Companies strive to reduce costs as low as possible including in paying taxes. Tax management is present as a bridge medium in minimizing tax payments without violating the Tax Law. The research that the author conducted was to conduct tax management planning for PT MAP Boga Adiperkasa Tbk in 2022. The research was conducted with a qualitative approach and data analysis with descriptive methods. The strategies carried out by the author to reduce the tax burden that must be paid by the company include a strategy to delay income, a strategy to maximize deductible costs, and a strategy to manage transactions related to providing employee welfare. The results of the research conducted by the researcher show that the company can save the tax burden from Rp. 36,842,250,000 to Rp. 16,889,000,000. This tax burden savings is very large for business entities which is worth Rp. 59,859,750 or with a percentage of 54%.